Foramen Magnum Meningioma: Microsurgical Endoscopic-Controlled Resection via a Lateral Suboccipital Retrocondylar Approach with Preservation of Posterior Arch of Atlas Integrity - Bassiouni, Hischam (J Neurol Surg B Skull Base, 2019)
Objective  Surgical treatment of foramen magnum (FM) meningiomas is challenging due to proximity of the tumor to critical neurovascular structures, namely, the lower brainstem/upper cervical cord, vertebral artery, PICA, and lower cranial nerves. Controversies in microsurgical resection of meningiomas in this location include the necessity for condyle drilling and the need for vertebral artery mobilization. However, a laminectomy or hemilaminectomy of the C1 posterior arch is usually routinely performed. We herein present microsurgical, endoscopic-controlled resection of a FM meningioma via a posterolateral retrocondylar suboccipital craniotomy with preservation of the integrity of the posterior arch of the atlas. Setting  Our patient, a 57-year-old patient, suffered from right-sided hemiparesis due to a right-sided ventrolateral FM meningioma compromising the medulla oblongata and upper cervical cord. The tumor at the craniocervical junction was resected through a posterolateral suboccipital retrocondylar craniotomy. Results  Radical resection of the FM meningioma was accomplished via a lateral suboccipital retrocondylar craniotomy with preservation of posterior arch of atlas integrity. The postoperative course was uneventful with full preservation of neurological function. Preoperative hemiparesis subsided completely after surgery. Conclusion  Anterior-laterally located FM meningiomas can be safely and completely resected via a suboccipital retrocondylar craniotomy. A laminectomy or hemilaminectomy of the posterior arch of C1 is not routinely required for complete and safe resection of these tumors at the craniocervical junction. Neuroendoscopy is beneficial for control of complete tumor resection. The link to the video can be found at: https://youtu.be/DBk6qoJ6OzQ .